Kick the can eaudiobook - Johnson, George Clayton (Twilight Zone Radio Dramas., 2013)
The senior residents of Sunnyvale decide that the secret to youth is acting young, and in particular playing a childhood game called "kick-the-can." One grumpy resident refuses to play and learns to regret it.